2014
DOI: 10.1186/1750-9378-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer burden among HIV-positive persons in Nigeria: preliminary findings from the Nigerian AIDS-cancer match study

Abstract: BackgroundAlthough Nigeria has a large HIV epidemic, the impact of HIV on cancer in Nigerians is unknown.MethodsWe conducted a registry linkage study using a probabilistic matching algorithm among a cohort of HIV positive persons registered at health facilities where the Institute of Human Virology Nigeria (IHVN) provides HIV prevention and treatment services. Their data was linked to data from 2009 to 2012 in the Abuja Cancer Registry. Match compatible files with first name, last name, sex, date of birth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 31 publications
(24 reference statements)
4
57
3
1
Order By: Relevance
“…This difference with the developed world may be as a result of differences in the prevalence of risk factors for cervical cancer such as early age at first intercourse [28], total number of lifetime sexual partners, sexual practices [29], and early age at first pregnancy [28]. The widespread availability of population based screening programs for cervical cancer in developed countries has also contributed to reduced incidence while HIV infection in Africa is contributing to increased incidence [30,31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference with the developed world may be as a result of differences in the prevalence of risk factors for cervical cancer such as early age at first intercourse [28], total number of lifetime sexual partners, sexual practices [29], and early age at first pregnancy [28]. The widespread availability of population based screening programs for cervical cancer in developed countries has also contributed to reduced incidence while HIV infection in Africa is contributing to increased incidence [30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Nigeria have found an association between cervical cancer and HIV [47,55]. A registry linkage study in Nigeria reported a twofold higher risk of cervical cancer in people living with HIV/AIDS [31]. A recent systematic review and meta-analysis revealed an excess risk of anal cancer among men who have sex with men (MSM), particularly among those who were HIV positive [56].…”
Section: Discussionmentioning
confidence: 99%
“…6,7,15,52 These studies could be conducted using the well-established HIV/AIDS–cancer record linkage methodology or via cohort or cross-sectional studies. 66-69 Etiological studies should also shed light on the interactions between different viral agents and other environmental factors on cancer development in this setting. This may be particularly relevant to childhood cancers.…”
Section: Research Priorities and Challengesmentioning
confidence: 99%
“…17,18 To inform cervical cancer screening programs for HIV-positive women in South Africa, data on ICC burden, associated risk factors, and the effect of screening programs on ICC risk in this specific population are needed. Whereas some ICC incidence rate estimates are available for HIV-positive women in sub-Saharan Africa, ranging from 8/100,000 pys to 259/100,000 pys, 1922 data on risk factors and the effect of cervical cancer screening on ICC risk are scarce for the African setting. Studies examining the effect of cervical cancer screening at the patient-level often do not have enough power to detect changes in ICC incidence rates.…”
Section: Introductionmentioning
confidence: 99%